Infection of Goose with Genotype VIId Newcastle Disease Virus of Goose Origin Elicits Strong Immune Responses at Early Stage - Xu, Qianqian; Chen, Yuqiu; Zhao, Wenjun; Zhang, Tingting; Liu, Chenggang; Qi, Tianming; Han, Zongxi; Shao, Yuhao; Ma, Deying; Liu, Shengwang (Frontiers in Microbiology, 2016)
Newcastle disease (ND), caused by virulent strains of Newcastle disease virus (NDV), is a highly contagious disease of birds that is responsible for heavy economic losses for the poultry industry worldwide. However, little is known about host-virus interactions in waterfowl, goose. In this study, we aim to characterize the host immune response in goose, based on the previous reports on the host response to NDV in chickens. Here, we evaluated viral replication and mRNA expression of 27 immune-related genes in 10 tissues of geese challenged with a genotype VIId NDV strain of goose origin (go/CH/LHLJ/1/06). The virus showed early replication, especially in digestive and immune tissues. The expression profiles showed up-regulation of Toll-like receptor (TLR)1–3, 5, 7 and 15, avian β-defensin (AvBD) 5–7, 10, 12 and 16, cytokines [interleukin (IL)-8, IL-18, IL-1β and interferon-γ], inducible NO synthase (iNOS), and MHC class I in some tissues of geese in response to NDV. In contrast, NDV infection suppressed expression of AvBD1 in cecal tonsil of geese. Moreover, we observed a highly positive correlation between viral replication and host mRNA expressions of TLR1-5 and 7, AvBD4-6, 10 and 12, all the cytokines measured, MHC class I, FAS ligand, and iNOS, mainly at 72 h post-infection. Taken together, these results demonstrated that NDV infection induces strong innate immune responses and intense inflammatory responses at early stage in goose which may associate with the viral pathogenesis.